Cognitive differences in second language learners and the critical period effects. - Figueiredo, Sandra (2018)
Research has shown a strong association between psychological, affective, neurological and learning variables, related also with age and gender factors, in the process of acquisition and/or learning of a second language. However, there is a theoretical controversy concerning the way the critical period may affect different levels of language competence. We developed an assessment instrument to test the phonological awareness and general cognitive achievement in L2, for application in L2 learners and also in monolinguals (natives). The goal is to predict the dimension of age (chronological age, age of acquisition, age of arrival) in the L2 literacy skills development. The data collected pertains to the first phase of a larger study and includes 64 students with migratory experience, acquiring Portuguese as L2. Findings in what concerns the decoding competence and the first language transference will be discussed, regarding particularly the results from some of the tests: alphabetic ordinance, phonemic blending, alliteration judgement and dichotic hearing The achievement observed shows that children present lower levels of accuracy in L2 context than expected, not regarding the positive levels at the alliteration judgment task, which is not an evidence of phonological awareness (in the consciousness sense). Alliteration, rime and rhyme judgment are symptoms of normative phonological knowledge, which is not necessarily phonological awareness, and based on the imitation ability toward verbal stimuli. The age factor remains as the main predictor of skill and ability and the mastery exhibited by the adult learners on particular levels of L2 phonology decoding does not confirm the theoretical from the critical period hypothesis, which generates the research interest into the theory revision and new insights related to educative orientations.